Writing and the Recognition of Customary Law in Premodern India and Java. - LUBIN, TIMOTHY (Journal of the American Oriental Society)
Explaining what made ancient Greek law unusual, Michael Gagarin observes that most premodern legal cultures "wrote extensive sets (or codes) of laws for academic purposes or propaganda but these were not intended to be accessible to most members of the community and had relatively little effect on the actual operation of the legal system." This article addresses the implications of writing for customary or regional law in South and Southeast Asia. The textual tradition of Dharmaśāstra ("Hindu law"), which canonizes a particular model of Brahmin customary norms, can certainly be called a "scholarly" exercise, and it was also intended as propaganda for the Brahmanical cosmopolitan world order. But it also formulated a procedural principle to recognize the general validity of other, even divergent, customary norms, though for the most part such rules remained lex non scripta. On the other hand, inscriptions provide evidence that writing was used for diverse legal purposes and offers glimpses of actual legal practice. In these records, customary laws are sometimes laid down as statutes by decree of a ruler or community body, or are simply invoked as long-established customary rules. But even when Dharmaśāstra texts are not directly cited, their influence over the longue durée is discernable in the persistence of śāstric legal categories and terms of art. This influence is even more evident in Java, where legal codes on the Dharmaśāstra model were composed in Javanese, and where the inscriptions came to exhibit a closer connection with śāstric discourse than is found in India.